Crustal Fault Connectivity of the Mw 7.8 2016 Kaikōura Earthquake Constrained by Aftershock Relocations. Issue 12 (26th June 2019) - Lanza, F.; Chamberlain, C. J.; Jacobs, K.; Warren‐Smith, E.; Godfrey, H. J.; Kortink, M.; Thurber, C. H.; Savage, M. K.; Townend, J.; Roecker, S.; Eberhart‐Phillips, D.
Abstract: The 14 November 2016 Mw 7.8 Kaikōura earthquake in the northern South Island, New Zealand, involved highly complex, multifault rupture. We combine data from a temporary network and the permanent national seismograph network to repick and relocate 2, 700 aftershocks of M≥3 that occurred between 14 November 2016 and 13 May 2017. Automatic phase‐picking is carried out using REST, a newly developed hybrid method whose pick quality is assessed by comparing automatic picks for a subset of 138 events with analysts' picks. Aftershock hypocenters computed from high‐quality REST picks and a 3‐D velocity model cluster almost exclusively in the shallow crust of the upper plate and reveal linkages at depth between surface‐rupturing fault segments. Only eight aftershocks are relocated on a deeper structure positioned between patches of geodetically detected afterslip. This indicates that afterslip has not triggered significant earthquake activity on the subduction interface during the period of aftershock activity analyzed. Plain Language Summary: Earthquake locations are fundamental for understanding the physics of earthquakes, defining the orientations and geometries of faults that have slipped seismically, and assisting in seismic hazard forecasting and assessment. We have mapped the locations of approximately 2, 700 of the largest aftershocks that followed the 14 November 2016 Mw 7.8 Kaikōura earthquake in the northern South Island, New Zealand. We achieve improvements in the precision and accuracy of the earthquakes' relocated hypocenters in two ways: (1) by using an expanded seismic network that incorporates data from more stations and (2) by applying a new automatic picking methodology that produces better seismic wave arrival time estimates. Our results show that most of the seismic energy released in the 6 months following the mainshock was generated in the uppermost 20 km of the crust, with the aftershocks' locations suggesting that separate faults mapped at the surface are in fact continuous at greater depth. Very little earthquake energy is associated with the subduction interface. Key Points: Aftershocks of M≥3 following the 2016 M7.8 Kaikōura earthquake are relocated using data from temporary and permanent seismic networks Aftershocks almost exclusively cluster in the shallow crust and are laterally more continuous than mapped surface ruptures Shallow (<10‐km depth) aftershocks highlight linkages at depth between surface‐rupturing fault segments